2014
DOI: 10.1002/2013gl058649
|View full text |Cite
|
Sign up to set email alerts
|

Thermal alteration: A possible reason for the inconsistency between OMEGA/CRISM and TES detections of phyllosilicates on Mars?

Abstract: Previous laboratory analyses have shown that high temperatures can modify the crystal structures of some phyllosilicates in such a way that their spectroscopic signatures appear different from various wavelength perspectives. This may be the case in the Nili Fossae region of Mars, where our analyses indicate that thermally altered (~400°C) Fe-rich smectites might be possible mineral analogs to the phyllosilicate-bearing units in addition to mineral assemblages formed by Fe/Mg smectite and amorphous weathering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This supports the hypothesis that phyllosilicates in Nili Fossae are old and might have been structurally disordered by impacts, rather than generated by them [e.g., Michalski et al, 2010]. More recently, Che and Glotch [2014] directly matched TES phyllosilicate spectra in the Nili Fossae region with the laboratory emissivity spectra of thermally altered nontronite heated to~400°C using a factor analysis and target transformation (FATT) algorithm [Thomas and Bandfield, 2013]. These results directly support our hypothesis that impact-induced structural disorder may contribute to the ambiguity of phyllosilicate detections by MIR spectroscopic techniques.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…This supports the hypothesis that phyllosilicates in Nili Fossae are old and might have been structurally disordered by impacts, rather than generated by them [e.g., Michalski et al, 2010]. More recently, Che and Glotch [2014] directly matched TES phyllosilicate spectra in the Nili Fossae region with the laboratory emissivity spectra of thermally altered nontronite heated to~400°C using a factor analysis and target transformation (FATT) algorithm [Thomas and Bandfield, 2013]. These results directly support our hypothesis that impact-induced structural disorder may contribute to the ambiguity of phyllosilicate detections by MIR spectroscopic techniques.…”
Section: Introductionsupporting
confidence: 75%
“…Indeed, it has been demonstrated by laboratory spectroscopy and modeling that preexisting phyllosilicates can survive postimpact exhumation temperatures [ Fairén et al , ], but not without minor thermal alteration, and near‐infrared (NIR) spectral features from Toro crater ejecta have been found to be consistent with thermally treated nontronite [ Gavin and Chevrier , ]. In addition, a unique spectral feature centered at 450 cm −1 in Mars Global Surveyor Thermal Emission Spectrometer (TES) data and associated with the detections by the Mars Express/Observatoire pour la Minéralogie, l'Eau, les Glaces et l'Activité (OMEGA) VNIR imaging spectrometer of nontronite‐rich deposits around Nili Fossae [ Michalski et al , ], has been shown to be consistent with nontronite after thermal alteration to 400°C [ Che and Glotch , ]. A detailed examination of the effects of shock metamorphism on clay mineral spectroscopy may thus provide valuable insights for the analysis and interpretation of Martian remote sensing data.…”
Section: Introductionmentioning
confidence: 99%
“…To identify spectral end‐members, we also use factor analysis and target transformation (FATT) [ Malinowski , ], a statistical principal component‐based approach. This method has been primarily applied to mid‐IR remote sensing data sets [ Bandfield et al ., ; Glotch et al ., ; Glotch and Rogers , ] but has recently been successfully applied to VNIR remote sensing data sets from Mars and the Moon [ Thomas and Bandfield , ; Che and Glotch , ; Friedlander et al ., ]. Factor analysis can be applied to any data set with independently varying components that add linearly.…”
Section: Data Sets and Methodsmentioning
confidence: 99%
“…Spectra of submarine terrestrial clays were compared to available CRISM spectra of Martian clays; the results showed that the largest group of clays (smectitic samples with FeO/MgO ratios ≈10-30, supposedly between submarine and low-submarine environment) were found on the Noachian highlands of Mars (Michalski et al, 2015) where no ocean was ever reported or possibly be present. Even the presence of smectite is not unambiguously the proof of formation in ponding water (Ehlmann et al, 2013) and might be the result of thermal alteration by lava instead (Che & Glotch, 2014). Another possibility is that phyllosilicates were formed by >400 °C hot hydrothermal fluids under the surface (Ehlmann et al, 2011), where the lithostatic pressure of the rocks still allows the stability of liquid water, and then exposed as outcrops upon erosion or transport by subsequent lava flows (Leone, 2017).…”
Section: Mineralogical Argumentsmentioning
confidence: 99%